Association between circulating ECM-associated molecules and cardiovascular outcomes in hemodialysis patients: a multicenter prospective cohort study - Hyeon Seok Hwang; Jihyun Baek; So-Young Lee; Hye Yun Jeong; Jin Sug Kim; Yang Gyun Kim; ShinYoung Ahn; Kipyo Kim; Seok Hui Kang; Min-Jeong Lee; Dong-Young Lee; Yu Ho Lee (BMC, 2024)
Abstract Hemodialysis patients are susceptible to cardiovascular remodeling, which increases the risk of cardiovascular morbidity and mortality. Circulating extracellular matrix (ECM)-associated molecules increase during cardiovascular remodeling and can be potential biomarkers of adverse cardiovascular outcomes. However, their clinical significance in patients undergoing hemodialysis remain unclear. This study aimed to elucidate the association between circulating ECM-associated molecules and cardiovascular outcomes in patients undergoing hemodialysis. To this end, we measured levels of plasma matrix metalloproteinase (MMP)-2, MMP-9, tenascin-C, and thrombospondin-2 in 372 patients with hemodialysis. Plasma MMP-2 levels were significantly higher in patients with future cardiovascular events than in those without future cardiovascular events (P = 0.004). All measured molecules had significant correlations with amino-terminal pro-brain natriuretic peptide levels, but the correlation coefficient was the strongest for plasma MMP-2 (rho = 0.317, P < 0.001). High plasma MMP-2 levels were predictive of left ventricular (LV) diastolic dysfunction (adjusted odds ratio per a standard deviation increase = 1.48, 95% confidence interval [CI] = 1.05-2.08) and were independently associated with an increased risk of composite cardiovascular events (adjusted hazard ratio per a standard deviation increase = 1.30, 95% CI = 1.04-1.63). In conclusion, high plasma MMP-2 levels are associated with LV diastolic dysfunction and an increased risk of adverse cardiovascular outcomes in hemodialysis patients.